Jurnalis dan Jurnalisme Peka Konflik di Indonesia - Sunarni, Arni (Interaksi: Jurnal Ilmu Komunikasi, 2014)
Mass media has the ability to determine the thoughts, perceptions, opinions, and even peopleâ€™s behavior. Whether we realize it or not, journalists or media has a very significant role in the conflict. Media coverage does not always guarantee that the reporting sensitive and responsible. Therefore, journalists need to develop and implement conflict-sensitive journalism by giving attention to the public interest Conflict sensitive journalism is not a new form of journalism that aims to create special conditions in the community (such as â€œpeaceâ€), but rather an attempt or approach to produce quality reports with the basic values of journalism. Application of conflict sensitive journalism is pushing back against the practice of journalism alignment deviates.